Pengaruh Pengaruh Perilaku Oportunistik, Board Diversity, dan Financial Distress Terhadap Manajemen Laba Riil - Albert Irawan; Renna Magdalena (Jurnal Proaksi, 2025)
Main Purpose – This study examines the effect of opportunistic behavior, board diversity, and financial distress on reall earnings management practices.Method – This study used a population of all manufacturing companies listed on the Indonesia Stock Exchange from 2022 to 2024. The sample size for this study was 537. This study used secondary data from the Indonesia Stock Exchange website. The secondary data were audited financial statements. This study used the main model test, robust test, and additional test on the dependent variable of real earnings management, which was proxied by abnormal discretionary costs, abnormal production costs, and abnormal operating cash flow.Main Findings – Opportunistic behavior has no effect on abnormal discretionary costs; board diversity has no effect on abnormal discretionary costs; and financial distress has a negative effect on abnormal discretionary costs.Theory and Practical Implications – This study’s results develop a relationship between management methods (such as opportunistic behavior, board diversity, and financial distress) and real earnings management practices. Novelty – This study uses robust test and additional test to support the main research model that tests three proxies for real earning management.